A Kinect-Based 3d Hand-Gesture Interface for 3d Databases - Velastin-Carroza, S (Springer Verlag, 2015)
The use of natural interfaces improves significantly aspects related to human-computer interaction and consequently the productivity and the overall performance. In this paper we present a novel framework to interact with data elements presented in a 3D space. The system provides two mechanisms to interact using 2D and 3D gestures based on data provided by Kinect and on hand detection and gesture interpretation algorithms. The proposed architecture is analysed indicating that 3D interaction with information is possible, and provides advantages over a 2D interaction over the same problem. Finally, two sets of experiments were performed to evaluate 2D and 3D interaction styles based on natural interfaces focusing on traditional interaction with 3D databases. © 2014, OpenInterface Association.